Anti-ICOS mAb Targets Pathogenic IL-17A-expressing Cells in Canine Model of Chronic GVHD. Issue 5 (15th October 2020) - Parker, Maura H.; Stone, Diane; Abrams, Kraig; Johnson, Melissa; Granot, Noa; Storb, Rainer
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Chronic graft-versus-host disease (GVHD) is a significant cause of morbidity and mortality in transplant patients. We have previously shown that 3 doses of an anti-inducible costimulator (ICOS) mAb transiently ameliorated symptoms and extended survival of dogs affected by chronic GVHD over that of control dogs. The purpose of this study was to specifically correlate changes in T-cell populations in the peripheral blood with anti-ICOS treatment and chronic GVHD progression and regression to reach a better understanding of the mechanism of the disease and prioritize future studies. Methods: Peripheral blood cells from canines transplanted with DLA-mismatched bone marrow and peripheral blood mononuclear cells to generate chronic GVHD were analyzed by flow cytometry using a panel of antibodies specific to helper and cytolytic T cells. Results: Chronic GVHD was specifically associated with an increase in CD4 + ICOS + cells, ICOS + cells expressing IL-17A, and CD8 + cells generating granzyme B. Treatment with anti-ICOS mAb at onset of chronic GVHD symptoms specifically targeted IL-17A + -expressing cells, transiently relieved symptoms, and lengthened survival but was unable to reduce the percentage of CD8 + T-cells expressing granzyme B. Conclusions: These studies suggested a role for both CD4 + and CD8 + T cells in pathogenesis of chronic GVHD in the canine model. We propose that future studies should focus on further extending survival by developing a treatment that would control both CD4 + and CD8 + T cells.